Staff Guidance Note on Macroprudential Policy. (Policy Papers; Policy Paper, 2014)
This note provides guidance to facilitate the staff's advice on macroprudential policy in Fund surveillance. It elaborates on the principles set out in the 'Key Aspects of Macroprudential Policy,' taking into account the work of international standard setters as well as the evolving country experience with macroprudential policy. The main note is accompanied by supplements offering Detailed Guidance on Instruments and Considerations for Low Income Countries.